The Relationship Between Physical Activity Levels and Cardiorespiratory Fitness Among Cadet Medical Students in The Undergraduate Medical Program Cohort 4 at The Republic of Indonesia Defense University - justin ibnu hakim munawar; Grace joselini corlesa; Roby syah putra firmansyah; Markus Wibowo; Nirawan Putranto; Disty Chania; Hanum zahra faras fadhilah; Antonius Reuben (Perkumpulan Kedokteran Militer, 2026)
Background: Physical activity plays a crucial role in maintaining cardiovascular and pulmonary health, especially for Cadet Medical Students who are required to achieve optimal physical fitness. However, it remains unclear whether the physical activity levels of Cadet Medical Students in the Undergraduate Medical Program Cohort 4 at the Republic of Indonesia Defense University meet the necessary fitness standards. Objective: This study aims to analyze the relationship between physical activity levels and cardiorespiratory fitness among cadet students. Methods: A quantitative cross-sectional design was employed, involving 72 respondents selected using a total sampling technique. Physical activity levels were assessed using the Bouchard Activity Diary, while cardiorespiratory fitness was evaluated through the 12-minute Cooper Test, which was converted into VO2max values. Result and Analysis: The results showed that the majority of respondents had moderate (81.9%) and vigorous (18.1%) physical activity levels. The distribution of cardiorespiratory fitness indicated that 45.5% of male respondents had VO2max classified as excellent, whereas among female respondents, the majority (53.8%) fell into the good category. Spearman’s correlation test revealed a significant positive relationship between physical activity levels and cardiorespiratory fitness (r = 0.585, p < 0.001). These findings indicate that higher physical activity levels are associated with better cardiorespiratory fitness. In conclusion, there is a significant correlation between physical activity levels and cardiorespiratory fitness among Cadet Medical Students in the Undergraduate Medical Program Cohort 4 at the Republic of Indonesia Defense University. These results highlight the importance of maintaining an optimal level of physical activity to improve cardiorespiratory.